(untitled) (Observatorio Económico, 2015)
In 2010, Chile implemented Law No. 20,257 to promote non-conventional renewable energy (NCRE) through a system of tradable quotas among firms. The law establishes that every firm withdrawing energy from the system must certify NCRE injections equivalent to 10% of those withdrawals. This obligation has been phased in over time: 5% between 2010 and 2014, rising by 0.5% per year from 2015 until reaching 10% in 2024.4. In addition, the law allows obligations and surpluses to be carried over for one calendar year. Continue reading...